Peran dan Strategi Pengembangan Subsektor Peternakan dalam Pembangunan Kabupaten Agam Sumatera Barat - Yulia Yulia; Lukman Mohammad Baga; Netti Tinaprilla (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
Agam District Government has the goal of improving economic growth rate of 5.94 percent in 2011 to 7.98 percent in 2017. However, the constraints experienced by the development of the animal husbandry sector is a decrease in the growth rate of the animal husbandry sector and the contribution to the GDP, it is necessary for the development of the animal husbandry subsector in Agam by taking into account various aspects. This study aims to analyze the potential and role of formulating priority strategies of alternative development strategy animal husbandry subsector. Results of the analysis of the animal husbandry subsector LQ is a commodity basis. The shift results proportional growth 10.72 percent negative growth. Region share growth of 2.33 percent. The results obtained from the alternative strategies SWOT matrix were analyzed using QSPM. development and coaching each region based on the existing potential (6.278), increasing the promotion and development of human resources breeder (5.773), to build and develop patterns of cooperation and mutual benefit (5.618), examination of animal health and disease prevention (5.406), implementation and development appropriate technology (5.330) and optimization in securing local resources (4.982). Selected strategic alternatives of highest appeal total development strategy as well as coaching is done each region based on the existing potential (6.278), then the suggestions can be made to the Government Agam namely increasing the number of livestock extension workers and attract investors to develop the livestock subsector in Agam District.